2006
DOI: 10.1111/j.1471-0528.2006.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

First aid for obstetric haemorrhage: the pilot study of the non‐pneumatic anti‐shock garment in Egypt

Abstract: Objective To compare the effect of non-pneumatic anti-shock garment (NASG) on blood loss from obstetric haemorrhage with standard management of obstetric haemorrhage.Design Observational study of consecutive obstetric haemorrhage cases before and after introduction of the NASG.Setting Four tertiary care maternity facilities in Egypt.Sample The sample consisted of women with obstetric haemorrhage and signs of shock and the entry criteria were: >750 mL of blood loss and either pulse of >100 beats per minute or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 6 publications
2
43
2
1
Order By: Relevance
“…Ensure patient's airway is patent and give oxygen. Several studies including this work have confirmed the effectiveness of the NASG as a first-aid-lifesustaining-device that can sustain the lives of critical ill shock patients until cross matched blood and definitive interventions become available [12][13][14][15][16][17]. The normal saline infusion was limited to 1.5 liter instead of the usual recommendation of 3:1 to avoid fluid overload as the vascular volume is restricted by the NASG application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensure patient's airway is patent and give oxygen. Several studies including this work have confirmed the effectiveness of the NASG as a first-aid-lifesustaining-device that can sustain the lives of critical ill shock patients until cross matched blood and definitive interventions become available [12][13][14][15][16][17]. The normal saline infusion was limited to 1.5 liter instead of the usual recommendation of 3:1 to avoid fluid overload as the vascular volume is restricted by the NASG application.…”
Section: Discussionmentioning
confidence: 99%
“…It is a lower body suit of articulated neoprene and Velcro segments that provides rapidly lower body circumferential counter pressure of 20-40 mmHg that decreases the distal aortic mean baseline blood flow of 1.99 l/min by 0.65, and thus shunts blood flow from the lower limbs and the pelvis to the heart, brain, lungs and kidneys like during the compensatory stage of hypovolemic shock [13,14]. Studies in Egypt and Nigeria on obstetric hemorrhage confirmed that the NASG can reduce pelvic blood loss by 50%, prevent emergency hysterectomy, and shock-related morbidities like irreversible shock, multiple organ failures and maternal deaths [15][16][17]. The aims of this study are to reappraisal the effectiveness of NASG in averting maternal deaths and shock-related morbidities in severe obstetric hemorrhagic shock patients, and to make recommendations.…”
Section: Introductionmentioning
confidence: 94%
“…14,15 Larger pre-post studies in Egypt and Nigeria indicate that NASG use can significantly reduce maternal mortality and extreme adverse outcomes (EAO) (maternal death or severe maternal morbidity). In Nigeria, the relative risk (RR) of mortality in the NASG intervention phase, compared to the pre-intervention phase was 0.32 (95% confidence interval [CI] 0.14-0.72), 16 and in Egypt, the RR of EAO with the NASG was 0.36 (95% CI 0.16-0.80).…”
Section: Introductionmentioning
confidence: 99%
“…Case studies and case series have, however, been published and summarized (81)(82)(83)(84)(85)(86)(87). The use of nonpneumatic antishock garments (NASGs) has been reported in a before-and-after study of 634 women with obstetric haemorrhage (43% with uterine atony) in Egypt (88).…”
Section: Summary Of Evidencementioning
confidence: 99%